The Dinosaurs Are Back and It's All Your Fault Edward! - Wendy Hartmann (New York Aladdin Paperbacks, 2000)
Believing that his older brother's silly stories about dinosaurs are true, Edward prepares for the worst, in this funfilled tale with a dramatic ending. Reprint.
Keywords: Read Aloud -- Read Aloud